2022
DOI: 10.3389/fneur.2022.880944
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Ketogenic Diet for Mitochondrial Disease With Epilepsy: A Prospective, Open-labeled, Controlled Study

Abstract: BackgroundThe ketogenic diet (KD) is increasingly used to treat drug-resistant epilepsy because of its favorable effect on seizure reduction. Patients with mitochondrial diseases tend to experience seizures. Therefore, this study aimed to test the efficacy of the KD on participants with mitochondrial diseases in a controlled trial.MethodsParticipants from fourteen clinical centers who were diagnosed with mitochondrial disease were semi-randomized to either the intervention (KD) or control group. The KD group f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…While efforts to define the therapeutic potential of ketogenic diet in genetic mitochondrial disease are ongoing, recent studies indicate that dietary ketosis may attenuate mitochondrial epilepsies but does not benefit overall disease course in mitochondrial disease. [13][14][15] Given these data, our findings here further suggest that use of a ketogenic diet in mitochondrial disease should be carefully considered. These results may also have some bearing on the practice of fasting mitochondrial patients prior to anesthetic exposure, as a fasting induced ketogenic state may similarly impact anesthesia.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…While efforts to define the therapeutic potential of ketogenic diet in genetic mitochondrial disease are ongoing, recent studies indicate that dietary ketosis may attenuate mitochondrial epilepsies but does not benefit overall disease course in mitochondrial disease. [13][14][15] Given these data, our findings here further suggest that use of a ketogenic diet in mitochondrial disease should be carefully considered. These results may also have some bearing on the practice of fasting mitochondrial patients prior to anesthetic exposure, as a fasting induced ketogenic state may similarly impact anesthesia.…”
Section: Discussionmentioning
confidence: 54%
“…Available evidence seems to support the notion that dietary ketosis is beneficial for mitochondrial disease related epilepsies, with mitochondrial ETC CI patients appearing to show the greatest benefits. 13,14 Dietary ketosis also appears to reduce seizure incidence in the Ndufs4(−/−) mouse model of Leigh syndrome. 15 However, studies to date do not seem to support the notion that overall disease progression is altered by a ketogenic diet in either the Ndufs4(−/−) model or patients, suggesting that benefits may be limited to seizure control.…”
Section: Introductionmentioning
confidence: 98%
“…Dietary therapies can also be associated with additional benefits such as an improvement in cognition [34][35][36]. A meta-analysis found 19 studies that reported some cognitive improvement following the initiation of the ketogenic diet [35].…”
Section: Benefits Beyond Seizure Controlmentioning
confidence: 99%
“…Response rates were higher in patients with MELAS or pathogenic variants in mtDNA. In conclusion, the ketogenic diet has been proven to be safe and effective for seizure control in primary mitochondrial diseases, especially MELAS and mtDNA pathogenic variants [ 76 ]. Interestingly, the ketogenic diet seems to be contraindicated for treatment of mitochondrial myopathy related to mtDNA multiple deletions.…”
Section: Managementmentioning
confidence: 99%
“…Interestingly, the ketogenic diet seems to be contraindicated for treatment of mitochondrial myopathy related to mtDNA multiple deletions. Although data, so far, are too scarce for general guidelines, it is still recommended to consider a ketogenic diet in patients with resistant mitochondrial epilepsy, initiated by an experienced team [ 75 , 76 ].…”
Section: Managementmentioning
confidence: 99%